Sistem Informasi Manajemen Komunitas Berbasis Web (Studi Kasus: Itb Stikom Bali Kampus Jimbaran) - Saputra, I Gede Seri Dharma Bobby; Setiawan, I Made Oka Adi; Sudiatmika, I Putu Gede Abdi; Pramartha, Nyoman Bagus; Artana, Wayan Widya (Jurnal SUTASOMA (Science Teknologi Sosial Humaniora), 2024)
ITB STIKOM Bali Community Jimbaran Campus is a forum for students to channel their talents and interests. Each Community has one coordinator who functions to manage members from each community. To facilitate the work of each coordinator in managing member data, activities and events, good management is needed. Management is a process in which a person can manage everything that is done by individuals or groups. The purpose of this research is to build a Web-Based Community Management Information System that can manage member data, activities and events from each community and make it easier for students to find information about the communities they participate in. In designing and building this system, the author uses the PHP programming language with the CodeIgniter framework. The design method used is the waterfall method starting from the system analysis stage and system design. The results obtained after doing blackbox testing on the system that has been made show that the functional system is running well. The results of the questionnaire from the user side of the Web-Based Community Management Information System get a percentage of a total of 86% which is categorized as "Very Good" with a total average value of 4.3 which means very good in implementing the system from 36 respondents' answers, while in terms of The admin on the Web-Based Community Management Information System gets a percentage of 79% in total which is categorized as "Good" with a total average value of 3.95 which means good in implementing the system from 10 respondents' answers.